2022
DOI: 10.1177/09579265221117014
|View full text |Cite
|
Sign up to set email alerts
|

Discursive construction of migrant otherness on Facebook: A distributional semantics approach

Abstract: This work aims to study the construction of migrant categories and immigration discourse on Swedish-speaking Facebook pages in the last decade. It combines the insights from computational linguistics and distributional semantics approach with those from discursive psychology to explore a corpus of more than 1 M Facebook posts. This allows one to compare the meanings of labels denoting various categories of migrants and identify the key interpretative repertoires used to discuss the immigration topic. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…For example, some may have expatriates with high-paid jobs in mind when discussing immigration, whereas others may primarily be thinking about refugees-these differences in imagination result in people expressing different attitudes or debating the topic differently. For example, Yantseva (2023) has found that immigrants are more associated with costs and threats to society than refugees using text collected from Swedish Facebook. The empirical essays in this thesis largely ignore potential issues related to imagined immigration by studying the meaning of immigration as a single concept rather than exploring the importance attached to specific migrant types, such as refugees, labor migrants, asylum seekers, or minority groups such as Muslims, the Sámi people, or Eastern Europeans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some may have expatriates with high-paid jobs in mind when discussing immigration, whereas others may primarily be thinking about refugees-these differences in imagination result in people expressing different attitudes or debating the topic differently. For example, Yantseva (2023) has found that immigrants are more associated with costs and threats to society than refugees using text collected from Swedish Facebook. The empirical essays in this thesis largely ignore potential issues related to imagined immigration by studying the meaning of immigration as a single concept rather than exploring the importance attached to specific migrant types, such as refugees, labor migrants, asylum seekers, or minority groups such as Muslims, the Sámi people, or Eastern Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on Flashback has found that Muslims are discussed as an outgroup that is in conflict with Swedish culture and values (Törnberg and Törnberg 2016). Frames on Flashback during the "refugee crisis" have been suggested to have been more emotional than those found in the traditional news media during the same period (Yantseva 2020). Furthermore, Flashback plays a crucial role in relation to radical right-wing political violence, e.g., with posts encouraging the burning of refugee centers (Wahlström and Törnberg 2021).…”
Section: The Online Publicmentioning
confidence: 99%